A rare skin infection in atopic dermatitis: A case report. Issue 12 (14th September 2020) - Malara, Giovanna; Trifirò, Caterina; Bartolotta, Annunziata; Conte, Marco; Denisi, Pietro
Abstract: Atopic dermatitis is associated with a susceptibility to infection usually by Staphylococcus spp due to a decrease of AMPs and Th2 cytokines (eg, IL‐17). We reported a rare E. faecalis skin contamination in AD patients due to a frequent contact with excrement. Abstract : Atopic dermatitis is associated with a susceptibility to infection usually by Staphylococcus spp due to a decrease of AMPs and Th2 cytokines (eg, IL‐17). We reported a rare E. faecalis skin contamination in AD patients due to a frequent contact with excrement.